Shifting the half wave dipole antenna resonance using EBG structure - El Ghabzouri, Mohammad E. (2015)
In this paper, the main motivation is to introduce a new behavior of the electromagnetic band gap (EBG) structures, it is a significant shifting the resonance frequency down of the dipole antennas, this very interesting and useful technique led to low profile, in addition to performance enhancement of dipole antennas, either on return loss or radiation pattern. Also among this EBG structure an investigation on specific absorption rate (SAR) is shown. The used dipole antenna is resonating around 3.5GHz (part of 4G bands), then by using this technique we could shift the working frequency of the same dipole antenna to 2.8GHz worldwide interoperability for microwave access (WiMAX), this new resonance is 80% lower compared with the normal resonance without any structure. The principle of this new technique still valid with other frequency, depending on the frequencies that we would like to shift the working frequency between.